Manufacturing method of polystyrene resin extruded foam board

The method addresses the challenges of moldability and thermal conductivity in polystyrene-based resin extruded foam plates by using a specific blend of HFO-1336mzz and saturated hydrocarbons, resulting in foam plates with improved smoothness, low thermal conductivity, and manufacturing stability.

JP7667730B2Active Publication Date: 2025-04-23JSP CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021200029
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-12-09
Publication Date
2025-04-23
Estimated Expiration
2041-12-09

AI Technical Summary

Technical Problem

When manufacturing polystyrene-based resin extruded foam plates, excessive use of HFO-1336mzz as a foaming agent can lead to separation from the resin, deteriorating moldability, and combining HFO-1336mzz with other foaming agents can further complicate blending ratios, especially for thick foam plates with large cross-sectional areas.

Method used

A manufacturing method involving a specific composition of physical blowing agents, including 1,1,1,4,4,4-hexafluoro-2-butene (HFO-1336mzz) and saturated hydrocarbons like isobutane, within defined mole ratios, is used to produce polystyrene-based resin extruded foam plates. This method ensures good smoothness, low thermal conductivity, and manufacturing stability by optimizing the foaming process.

Benefits of technology

The method achieves foam plates with excellent smoothness, low thermal conductivity, and improved manufacturing stability, even for large cross-sectional areas, by maintaining the optimal balance of foaming agents and their ratios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667730000001
    Figure 0007667730000001
Patent Text Reader

Abstract

To provide a method for manufacturing a polystyrene-based resin extruded foamed plate which has appearance having good smoothness, can maintain low thermal conductivity, and is excellent in manufacture stability.SOLUTION: A method for manufacturing a polystyrene-based resin extruded foamed plate, which has a cross sectional area of 100 cm2 or more and apparent density of 20-50 kg / m3, includes a step of extruding a foamable resin composition obtained by kneading a base material resin containing a polystyrene-based resin as a main component, a flame retardant, and a physical foaming agent, and molding the extruded resin composition into a plate shape by a molding tool, wherein the physical foaming agent contains 1,1,1,4,4,4-hexafluoro-2-butene, and saturated hydrocarbon having 3 to 5 carbon atoms.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an extruded polystyrene foam board, and more particularly to a method for producing an extruded polystyrene foam board that can be suitably used as an insulating material for the walls, floors, roofs, etc. of buildings. [Background technology]

[0002] Polystyrene resin extruded foam boards (hereinafter, simply referred to as "foam boards") are widely used as building insulation materials due to their excellent thermal insulation properties and mechanical strength. Such foam boards are generally produced by heating and melting polystyrene resin in an extruder, then injecting a physical foaming agent into the resulting molten material, kneading the resulting foamable molten resin mixture, and extruding the mixture into a low pressure region through a flat die or the like attached to the tip of the extruder to foam it, and forming the mixture into a plate shape using a molding tool.

[0003] The typical foaming agent used in the manufacture of the foamed board is butane such as normal butane or isobutane, which has excellent foaming properties, an ozone depletion potential of 0, a small global warming potential, excellent heat insulation, etc. However, these butanes are highly flammable and remain in the foamed board for a long period of time, making it difficult to achieve a high level of flame retardancy as specified in the flammability test method of JIS A9521:2017, and therefore there is an upper limit to the amount of butane added.

[0004] In order to solve the above problems, blowing agents made of hydrofluoroolefins (hereinafter, simply referred to as "HFOs") such as 1,3,3,3-tetrafluoropropene and 1-chloro-3,3,3-trifluoropropene have been used in recent years (for example, Patent Documents 1 and 2). These HFOs are non-flammable, have low thermal conductivity, and can provide high thermal insulation. Furthermore, they are environmentally friendly blowing agents because they have very small ozone depletion potential and global warming potential.

[0005] In Patent Documents 1 and 2, 1,1,1,4,4,4-hexafluoro-2-butene (HFO-1336mzz) is used as the HFO, either alone or in combination with other blowing agents. The HFO-1336mzz used in Patent Documents 1 and 2 is excellent in maintaining the thermal conductivity of the foam board low for a long period of time (long-term low thermal conductivity). Therefore, there is a demand for the production of a foam board that can maintain low thermal conductivity by using HFO-1336mzz as a blowing agent. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Special Publication No. 2010-522808 [Patent Document 2] Special Publication No. 2019-515112 Summary of the Invention [Problem to be solved by the invention]

[0007] However, when manufacturing a foam board, if the amount of HFO-1336mzz is excessively set in an attempt to maintain a lower thermal conductivity, the foaming agent separates from the resin, causing deterioration in moldability, and when HFO-1336mzz is used in combination with other foaming agents, the moldability may deteriorate depending on the blending ratio. These tendencies are particularly noticeable when attempting to obtain a foam with a large cross-sectional area, such as a thick foam board.

[0008] The present invention has been made in view of the above background, and an object of the present invention is to provide a method for producing an extruded polystyrene foam board having a good smooth appearance, capable of maintaining low thermal conductivity, and excellent production stability. [Means for solving the problem]

[0009] According to the present invention, there is provided a method for producing an extruded polystyrene resin foam board as described below. [1] A process for producing a foamable resin composition by kneading a base resin mainly composed of a polystyrene resin, a flame retardant, and a physical foaming agent, and extruding the extruded composition into a plate shape using a molding tool. 2 or more, and apparent density 20-50kg / m 3 A method for producing an extruded polystyrene foam board, comprising the steps of: The physical blowing agent contains 1,1,1,4,4,4-hexafluoro-2-butene and a saturated hydrocarbon having 3 to 5 carbon atoms, The total amount of the physical foaming agent is 1 to 1.5 mol, the amount of the 1,1,1,4,4,4-hexafluoro-2-butene blended is 0.1 to 0.6 mol per kg of the base resin; the amount of the saturated hydrocarbon having 3 to 5 carbon atoms is 0.2 to 0.7 mol per kg of the base resin, the total amount of the 1,1,1,4,4,4-hexafluoro-2-butene and the saturated hydrocarbon having 3 to 5 carbon atoms is 0.6 to 1.3 mol; The ratio of the amount (mol / kg) of the 1,1,1,4,4,4-hexafluoro-2-butene to the amount (mol / kg) of the saturated hydrocarbons having 3 to 5 carbon atoms (amount of 1,1,1,4,4,4-hexafluoro-2-butene / amount of saturated hydrocarbons having 3 to 5 carbon atoms) is 2 or less. [2] The method for producing an extruded polystyrene foam board according to the invention [1] above, wherein the ratio of the amount (mol / kg) of the 1,1,1,4,4,4-hexafluoro-2-butene to the amount (mol / kg) of the saturated hydrocarbon having 3 to 5 carbon atoms (amount of 1,1,1,4,4,4-hexafluoro-2-butene / amount of saturated hydrocarbon having 3 to 5 carbon atoms) is 1.5 or less. [3] The method for producing an extruded polystyrene foam board according to the invention [1] or [2], wherein the physical foaming agent contains one or more early-dissipation foaming agents selected from the group consisting of water, carbon dioxide, dialkyl ethers having 1 to 3 carbon atoms in the alkyl chain, and aliphatic alcohols having 1 to 5 carbon atoms, and the amount of the early-dissipation foaming agent is 0.2 mol or more per kg of the base resin. Effect of the Invention

[0010] According to the manufacturing method of the present invention, it is possible to provide a method for manufacturing an extruded polystyrene resin foam board that has a good appearance with good smoothness, can maintain low thermal conductivity, and has excellent manufacturing stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The method for producing an extruded polystyrene foam plate of the present invention will be described in detail below. The method for producing an extruded polystyrene foam board of the present invention includes a step of extruding a foamable resin composition obtained by kneading a base resin mainly composed of a polystyrene resin, a flame retardant, and a physical foaming agent, and forming the extruded resin composition into a board shape using a molding tool.

[0012] Specifically, a base resin consisting of a polystyrene resin and other resins added as necessary, a flame retardant, and other additives added as necessary are melted and kneaded under heating in an extruder, a foaming agent containing a specific HFO and saturated hydrocarbon is injected into the resulting molten mixture and further kneaded to form a foamable resin melt, the foamable resin melt is adjusted to an appropriate foaming temperature, and extruded from the high-pressure extruder to a low-pressure region through a flat die to foam, and a forming tool such as a forming die (for example, a shaping device (hereinafter also referred to as a guider) consisting of two upper and lower plates of polytetrafluoroethylene resin or the like installed in parallel or so as to expand gradually from the entrance to the exit direction) or a forming roll is arranged at the exit of the flat die, and the extruded foam composition is formed into a plate by passing through the forming tool. Note that in the present invention, by setting the blending amounts and blending ratios of the specific HFO and saturated hydrocarbon described later within specific ranges, it is possible to obtain a foamed plate that can be shaped into a plate and that has a good appearance and can maintain low thermal conductivity even when the foamed plate has a large cross-sectional area.

[0013] <Base resin> (Polystyrene resin) Examples of the polystyrene resin used in the production method of the present invention include polystyrene, styrene-methyl acrylate copolymers containing 50 mol% or more of styrene unit components, styrene-ethyl acrylate copolymers, styrene-methyl methacrylate copolymers, styrene-ethyl methacrylate copolymers, styrene-acrylic acid copolymers, styrene-methacrylic acid copolymers, styrene-maleic anhydride copolymers, styrene-polyphenylene ether copolymers, styrene-acrylonitrile copolymers, styrene-methylstyrene copolymers, styrene-dimethylstyrene copolymers, styrene-ethylstyrene copolymers, and styrene-diethylstyrene copolymers. Among these, polystyrene can be preferably used. In addition to the styrene unit component, polystyrene may contain a unit component derived from a branching agent such as a polyfunctional monomer or a polyfunctional macromonomer. The content of the styrene component unit in the copolymer is preferably 60 mol% or more, more preferably 80 mol% or more, and even more preferably 90 mol% or more.

[0014] The melt viscosity of the polystyrene resin used in the production method of the present invention is preferably 500 to 3000 Pa·s, more preferably 1000 to 2500 Pa·s, and even more preferably 1500 to 2300 Pa·s, in order to provide excellent foaming and moldability. Note that in this specification, the melt viscosity is measured based on JIS K7199:1999 at a temperature of 200°C and a shear rate of 100 sec -1 The values ​​were measured under the following conditions.

[0015] The base resin may contain an amorphous polyethylene terephthalate copolymer to enhance the heat insulation of the foam board. In this case, the amorphous polyethylene terephthalate resin is preferably blended in the base resin so as to be 5% by mass or more and less than 50% by mass, more preferably 10% by mass or more and 40% by mass or less, and even more preferably 15% by mass or more and 30% by mass or less. In the amorphous polyethylene terephthalate copolymer, the heat of fusion accompanying the melting of the resin based on JIS K7122 is less than 5 J / g. The heat of fusion is measured based on the heat flux differential scanning calorimetry method in JIS K7122-1987, using a heat flux differential scanning calorimeter, heating to 280°C at a heating rate of 10°C per minute, keeping at this temperature for 10 minutes, cooling to 23°C at a cooling rate of 10°C per minute, and heating again to 280°C at a heating rate of 10°C per minute.

[0016] The melt viscosity of the amorphous polyethylene terephthalate copolymer is preferably 500 to 3000 Pa·s, more preferably 1000 to 2500 Pa·s, and further preferably 1500 to 2300 Pa·s. From the viewpoint of compatibility with the polystyrene resin, the melt viscosity of the amorphous polyethylene terephthalate copolymer is preferably close to that of the polystyrene resin.

[0017] (Other polymers) The base resin may contain polymers other than the polystyrene resin and the amorphous polyethylene terephthalate copolymer within the scope of the present invention. Examples of other polymers include polyethylene resins (a mixture of one or more selected from the group consisting of ethylene homopolymers and ethylene copolymers having an ethylene unit content of 50 mol% or more), polypropylene resins (a mixture of one or more selected from the group consisting of propylene homopolymers and propylene copolymers having an ethylene unit content of 50 mol% or more), polyphenylene ether resins, and polymethyl methacrylate, as well as thermoplastic elastomers such as styrene-butadiene-styrene block copolymers, styrene-isoprene-styrene block copolymers, hydrogenated styrene-butadiene-styrene block copolymers, hydrogenated styrene-isoprene-styrene block copolymers, and styrene-ethylene copolymers. These other polymers may be blended according to the purpose so as to be less than 50% by mass in the base resin, preferably 30% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less.

[0018] In the manufacturing method of the present invention, a base resin mainly composed of a polystyrene-based resin means that 50% by mass or more of the base resin is a polystyrene-based resin, preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more.

[0019] <Physical foaming agent> The physical blowing agent used in the present invention contains blowing agent A consisting of 1,1,1,4,4,4-hexafluoro-2-butene (HFO-1336mzz) and blowing agent B which is a saturated hydrocarbon having 3 to 5 carbon atoms as essential components.

[0020] (Foaming agent A) Among hydrofluoroolefins, the foaming agent A, 1,1,1,4,4,4-hexafluoro-2-butene (HFO-1336mzz), has moderate solubility in polystyrene resins and excellent retention in the foam, making it possible to produce foamed boards with excellent long-term low thermal conductivity. In addition, since it is non-flammable, it can reduce the risk of ignition due to static electricity during foam board production. In addition, it has a low ozone depletion potential and a very small global warming potential, making it a foaming agent with a small burden on the environment. However, if too much foaming agent A is added, it may hinder smoothness and deteriorate the appearance.

[0021] (Foaming agent B) Examples of the saturated hydrocarbon having 3 to 5 carbon atoms as the blowing agent B include propane, normal butane, isobutane, normal pentane, isopentane, neopentane, cyclopentane, etc., which can be used alone or in combination of two or more. Among these, isobutane is preferably used.

[0022] The saturated hydrocarbons having 3 to 5 carbon atoms, especially isobutane, have a relatively slow gas permeation rate through polystyrene resin, so they can remain in the foam board for a relatively long time. In addition, the saturated hydrocarbons have a lower thermal conductivity than air, so when they remain in the bubbles of the foam board, they can contribute to reducing the thermal conductivity of the extruded foam board. However, they also inhibit the flame retardancy of the foam board, so it is necessary to consider the amount and ratio of the saturated hydrocarbons to achieve both flame retardancy and long-term heat insulation.

[0023] (Early-dissipating foaming agent) In the present invention, the above-mentioned blowing agent A and blowing agent B are used as essential blowing agents, but it is preferable to blend, as another blowing agent, one or more early-dissipation blowing agents selected from water, carbon dioxide, dialkyl ethers having an alkyl chain with 1 to 3 carbon atoms, and aliphatic alcohols having 1 to 5 carbon atoms.

[0024] Water has a small molecular weight and high foaming efficiency, which allows the apparent density of the extruded foam insulation board to be low. In addition, water reduces the environmental load and dissipates quickly from the foam board, allowing the dimensions of the resulting foam board to be stabilized quickly.

[0025] Carbon dioxide can achieve a high expansion ratio without inhibiting the flame retardancy of the resulting extruded foam insulation board, and since it has high gas permeability to the base resin, it quickly escapes from the extruded foam insulation board, making it possible to quickly stabilize the dimensional stability, insulating performance, and flame retardancy of the foam insulation board.

[0026] Dialkyl ethers having an alkyl chain with 1 to 3 carbon atoms and aliphatic alcohols having 1 to 5 carbon atoms do not destroy the ozone layer like water, do not cause global warming, and are quickly dispersed from the foamed board, allowing the shape of the foamed board to be quickly stabilized. Furthermore, by using dialkyl ethers having an alkyl chain with 1 to 3 carbon atoms and aliphatic alcohols having 1 to 5 carbon atoms, a foamed board with a lower apparent density (higher expansion ratio) can be obtained.

[0027] Examples of dialkyl ethers having an alkyl chain with 1 to 3 carbon atoms include dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, etc., and among these, dimethyl ether is preferably used. Two or more of these can also be used in combination.

[0028] Examples of the aliphatic alcohol having 1 to 5 carbon atoms include methyl alcohol (methanol), ethyl alcohol (ethanol), n-propyl alcohol, isopropyl alcohol, butyl alcohol, sec-butyl alcohol, tert-butyl alcohol, aryl alcohol, crotyl alcohol, propargyl alcohol, n-amyl alcohol, sec-amyl alcohol, isoamyl alcohol, tert-amyl alcohol, neopentyl alcohol, 3-pentanol, 2-methyl-1-butanol, 3-methyl-2-butanol, etc., and among these, ethanol can be preferably used. Two or more of these can also be used in combination.

[0029] By blending the early-dissipation foaming agent in a specific ratio with foaming agent A and foaming agent B, the resin is appropriately plasticized during foaming to improve the foamability, and a foamed board with a low apparent density can be obtained. When the early-dissipation foaming agent is used with foaming agent A and foaming agent B, it is preferable to use water and an aliphatic alcohol having 1 to 5 carbon atoms as the early-dissipation foaming agent, since it is easier to obtain a foamed board with a low apparent density. The molar ratio of water to the aliphatic alcohol having 1 to 5 carbon atoms (water:aliphatic alcohol having 1 to 5 carbon atoms) is preferably 65:35 to 85:15, and more preferably 70:30 to 80:20.

[0030] <Amount of foaming agent> In the present invention, the total amount of the physical foaming agent is 1 to 1.5 mol per kg of the base resin. From the viewpoint of obtaining a foamed board having excellent appearance, low apparent density, and capable of maintaining low thermal conductivity even after a long period of time, the total amount of the physical foaming agent is preferably 1.1 to 1.4 mol, more preferably 1.2 to 1.4 mol or more per kg of the base resin.

[0031] The amount of the foaming agent A is in the range of 0.1 to 0.6 mol per kg of base resin. By setting the amount of the foaming agent A in the above range, the thermal conductivity can be maintained low especially for a long period of time among foam boards using HFO. From the viewpoint of maintaining the thermal conductivity low for a long period of time, the amount of the foaming agent A is preferably 0.2 mol or more per kg of base resin, more preferably 0.3 mol or more. On the other hand, from the viewpoint of easily obtaining a foam board with a low apparent density, the amount of the foaming agent A is preferably 0.5 mol or less per kg of base resin, more preferably 0.4 mol or less. In the present invention, in a high-mixing extruder such as a screw or twin screw having a large ratio of the axial length of the screw to the diameter of the screw, or a tandem extruder in which a first extruder and a second extruder are connected in series, a continuous static mixer (static mixer) is used as necessary at the connecting portion between the first extruder and the second extruder or the connecting portion between the second extruder and the die, so that an extruded foam board can be easily produced when the amount of the foaming agent A is set in the above range.

[0032] The total amount of the foaming agent A and the foaming agent B is in the range of 0.6 to 1.3 mol, and preferably in the range of 0.7 to 1 mol, per 1 kg of the base resin.

[0033] The amount of foaming agent B is 0.2 to 0.7 mol per kg of base resin. If the amount of foaming agent B is too small, the desired low thermal conductivity may not be obtained. On the other hand, if the amount is too large, it may be difficult to achieve satisfactory flame retardancy. From this viewpoint, the amount of foaming agent B added is preferably 0.3 to 0.6 mol per kg of base resin.

[0034] Furthermore, the ratio of the amount of foaming agent A (mol / kg) to the amount of foaming agent B (mol / kg) (foaming agent A / foaming agent B) is 2 or less. In the present invention, it is important that the ratio of the amount of foaming agent A to the amount of foaming agent B satisfies the above-mentioned specific ratio. Even if foaming agent B is blended together with foaming agent A, if the ratio of the amount of foaming agent A to the amount of foaming agent B does not satisfy the above-mentioned specific ratio, the manufacturing stability is poor, and the obtained extruded foam board may have poor surface smoothness on the surface and edges, gas spots may occur, and the appearance may be poor. In addition, the bubble structure of the obtained extruded foam board may have an excessively small bubble diameter in the thickness direction, which may make it difficult to maintain a low thermal conductivity. From this viewpoint, the ratio of the amount of foaming agent A to the amount of foaming agent B is preferably 1.5 or less. On the other hand, the ratio of the amount of foaming agent A (mol / kg) to the amount of foaming agent B (mol / kg) (amount of foaming agent A / amount of foaming agent B) is preferably 0.1 or more, and more preferably 0.3 or more.

[0035] In the present invention, by setting the total amount of the foaming agents, the amount of foaming agent A, the amount of foaming agent B, and the ratio of the amount of foaming agent A to the total amount of foaming agents A and B within the above-mentioned specific ranges, it is possible to obtain an extruded foam board that has excellent moldability (shapeability) and a good appearance, even when a large amount of HFO is blended.

[0036] In addition, when an early-dissipation foaming agent is used as a foaming agent together with the foaming agent A and the foaming agent B, the amount of the early-dissipation foaming agent is preferably 0.2 mol or more per 1 kg of base resin. The early-dissipation foaming agent can improve the foamability and dissipates early, so that it does not inhibit the thermal conductivity or flame retardancy. From this viewpoint, the amount of the early-dissipation foaming agent is more preferably 0.3 mol or more, and even more preferably 0.4 mol or more, per 1 kg of base resin. On the other hand, from the viewpoint of maintaining a low thermal conductivity, the amount of the early-dissipation foaming agent is preferably 0.8 mol or less, and more preferably 0.7 mol or less.

[0037] <Other ingredients> (Flame retardant) The foamed board obtained by the manufacturing method of the present invention is mainly used as a heat insulating material for building materials, and flame retardancy is imparted by blending a flame retardant with the base resin. The flame retardant used in the present invention is not particularly limited, but it is preferable to use a brominated flame retardant. Examples of the brominated flame retardant include brominated butadiene-based polymers such as brominated butadiene-styrene copolymers, tetrabromobisphenol-A-bis(2,3-dibromo-2-methylpropyl ether), tetrabromobisphenol-S-bis(2,3-dibromo-2-methylpropyl ether), tetrabromobisphenol-F-bis(2,3-dibromo-2-methylpropyl ether), tetrabromobisphenol-A-bis(2,3-dibromopropyl ether), tetrabromobisphenol-B-bis(2,3-dibromopropyl ether), tetrabromobisphenol-C-bis(2,3-dibromopropyl ether), tetrabromobisphenol-D ... Examples of the brominated bisphenol compounds are brominated bisphenol compounds such as tetrabromobisphenol-S-bis(2,3-dibromopropyl ether) and tetrabromobisphenol-F-bis(2,3-dibromopropyl ether), and brominated isocyanurates such as tris(2,3-dibromopropyl)isocyanurate, mono(2,3,4-tribromobutyl)isocyanurate, di(2,3,4-tribromobutyl)isocyanurate, and tris(2,3,4-tribromobutyl)isocyanurate. These brominated flame retardants can be used alone or in combination.

[0038] In addition to these bromine-based flame retardants, nitrogen-containing cyclic compounds such as cresyl di-2,6-xylenyl phosphate, antimony trioxide, diantimony pentoxide, ammonium sulfate, zinc stannate, cyanuric acid, pentabromotoluene, isocyanuric acid, triallyl isocyanurate, melamine cyanurate, melamine, melam, and melem; silicone-based compounds; inorganic compounds such as boron oxide, zinc borate, and zinc sulfide; and phosphorus-based compounds such as phosphate esters represented by triphenyl phosphate, red phosphorus, ammonium polyphosphate, phosphazene, and hypophosphites.

[0039] Among these flame retardants, it is more preferable to use a flame retardant that combines tetrabromobisphenol A bis(2,3-dibromopropyl ether) and tetrabromobisphenol A bis(2,3-dibromo-2-methylpropyl ether), or a flame retardant that contains a brominated butadiene-styrene copolymer, because these can impart high flame retardancy, are less likely to decompose the polystyrene resin during extrusion, and make it easy to stably obtain a foamed board even when the foamed board has a low apparent density (high expansion ratio) and a large cross-sectional area.

[0040] The amount of the flame retardant is preferably 0.1 to 10 parts by mass, more preferably 1 to 9 parts by mass, and even more preferably 1.5 to 7 parts by mass, relative to 100 parts by mass of the base resin, since the amount can impart high flame retardancy to the foam board and can suppress deterioration of extrusion foamability and mechanical properties. If the amount is within this range, the flame retardant does not inhibit foamability, and a foam board having high flame retardancy such as the flammability standard for extruded polystyrene foam insulation described in "Test Method A" specified in the flammability test method of JIS A9521:2017 can be obtained.

[0041] (Flame retardant assistant) In the method of the present invention, a flame retardant auxiliary can be used in combination with the flame retardant to further improve the flame retardancy of the foam board. Examples of the flame retardant auxiliary include one or more selected from diphenylalkanes and diphenylalkenes such as 2,3-dimethyl-2,3-diphenylbutane, 2,3-diethyl-2,3-diphenylbutane, 3,4-dimethyl-3,4-diphenylhexane, 3,4-diethyl-3,4-diphenylhexane, 2,4-diphenyl-4-methyl-1-pentene, and 2,4-diphenyl-4-ethyl-1-pentene, and polyalkylated aromatic compounds such as poly-1,4-diisopropylbenzene. The amount of the flame retardant auxiliary is generally 0.01 to 1 part by mass, more preferably 0.05 to 0.5 parts by mass, based on 100 parts by mass of the base resin.

[0042] (Radiation suppressant) In the manufacturing method of the present invention, graphite can be blended as a radiation suppressant in the foamable resin composition in order to improve the heat insulating property. Graphite can improve the heat insulating property of the foam board by reflecting infrared rays.

[0043] Examples of graphite include flake graphite, scaly graphite, artificial graphite, and earthy graphite, and it is preferable to use graphite whose main component is flake graphite. As described later, it is preferable to use graphite as a master batch in which the graphite is mixed at a high concentration with a polystyrene resin. Graphite having a fixed carbon content of 80% or more is preferable because it has good workability when producing a master batch and has an excellent effect of improving the heat insulation of the resulting foam board. In addition, in order to further improve the heat insulation of the foam board, graphite having a fixed carbon content of 90% or more is more preferable, and graphite having a fixed carbon content of 95% or more is even more preferable. The fixed carbon content of the graphite refers to a value measured by the method described in JIS M8511:2014.

[0044] When graphite is blended, the blending amount of graphite is preferably 0.2 to 10 parts by mass per 100 parts by mass of the base resin. When the blending amount is within this range, the heat insulating property is improved, and a foam board having a desired low thermal conductivity can be obtained. From this viewpoint, the blending amount of the graphite is more preferably 0.3 parts by mass or more, and even more preferably 0.4 parts by mass or more, per 100 parts by mass of the base resin of the foam board. On the other hand, from the viewpoint of maintaining the flame retardancy of the foam board, the upper limit of the blending amount of graphite is more preferably 5 parts by mass, even more preferably 3 parts by mass, and particularly preferably 1 part by mass, per 100 parts by mass of the base resin of the foam board.

[0045] In addition, in the manufacturing method of the present invention, the foam board can contain a radiation suppressor other than the graphite in order to further improve the heat insulation. Examples of the radiation suppressor other than graphite include one or more selected from metal oxides such as titanium oxide, metals such as aluminum, ceramics, carbon black, graphite, infrared shielding pigments, hydrotalcite, etc. Among these, titanium oxide is preferably used. The amount of the radiation suppressor other than graphite to be added is about 0.5 to 5 parts by mass, more preferably 1 to 4 parts by mass, based on 100 parts by mass of the base resin.

[0046] In the method of the present invention, other known additives may be appropriately blended with the base resin as necessary, such as a cell regulator, a colorant such as a pigment or a dye, a heat stabilizer, a filler, and the like.

[0047] (Foam regulator) In the manufacturing method of the present invention, it is preferable to form a foamable resin composition by blending a bubble regulator with the base resin. As the bubble regulator, inorganic powders such as talc, kaolin, mica, silica, calcium carbonate, barium sulfate, titanium oxide, clay, aluminum oxide, bentonite, and diatomaceous earth can be used. Among them, talc is preferable because it is easy to adjust the bubble diameter and easy to reduce the bubble diameter without inhibiting flame retardancy, and fine talc with a 50% particle size (light transmission centrifugal sedimentation method) of 0.1 to 20 μm is particularly preferable, and fine talc with a 50% particle size (light transmission centrifugal sedimentation method) of 0.5 to 15 μm is particularly preferable. The amount of the bubble regulator to be added varies depending on the type of regulator, the target bubble diameter, etc., but when talc is used as the bubble regulator, it is preferably 0.1 to 7 parts by mass, more preferably 0.2 to 5 parts by mass, and even more preferably 0.3 to 3 parts by mass per 100 parts by mass of the base resin.

[0048] (Heat stabilizer) The thermal stabilizer can improve the thermal stability of the bromine-based flame retardant by blending it with raw materials or scraps when manufacturing a foam board or when recycling and repelletizing scraps of a foam board. Examples of the thermal stabilizer include one or more thermal stabilizers selected from bisphenol-type epoxy compounds and novolac-type epoxy compounds such as EPICLON series manufactured by DIC Corporation, hindered phenol compounds such as pentaerythritol tetrakis [3- (3,5-di-tert-butyl-4-hydroxyphenyl) propionate], and phosphite compounds such as bis (2,6-di-t-butyl-4-methylphenyl) pentaerythritol diphosphite. The blending amount of the thermal stabilizer is preferably 0.1 to 40 parts by mass with respect to 100 parts by mass of the total amount of the flame retardant.

[0049] In the manufacturing method of the present invention, as a method of blending the flame retardant and other additives into the base resin, a method of feeding a predetermined ratio of the flame retardant and other additives together with the base resin to a feed section provided upstream of the extruder and kneading them in the extruder can be adopted. In addition, a method of feeding the flame retardant and other additives into the molten resin from a feed section provided midway through the extruder can also be adopted. Specifically, a method of feeding a dry blend of the flame retardant, other additives, and base resin to the extruder and melt-kneading it, a method of feeding a molten kneaded product obtained by kneading the flame retardant, other additives, and base resin with a kneader or the like to the extruder, a method of preparing a master batch in which a high concentration of the flame retardant and other additives is blended in advance with the base resin, feeding this to the extruder and melt-kneading it with the base resin, and the like can be adopted. In particular, from the viewpoint of dispersibility, it is preferable to adopt a method of preparing a flame retardant master batch and feeding it to the extruder. The flame retardant masterbatch is prepared by using a polystyrene resin as a base resin having a melt flow rate of about 0.5 to 30 g / 10 min at 200° C. under a load of 5 kg, and adjusting the masterbatch so that the flame retardant content is 10 to 95 mass %, more preferably 30 to 90 mass %, and even more preferably 50 to 85 mass %.

[0050] <Physical properties of foam board> Next, the extruded polystyrene resin foam board obtained by the production method of the present invention will be described. (Cross-sectional area, dimensions, etc.) The foamed plate of the present invention is in the form of a plate, and its cross-sectional area perpendicular to the extrusion direction is 100 cm 2 More than 200cm 2 The upper limit of the cross-sectional area is approximately 1500 cm 2 In this specification, the cross-sectional area perpendicular to the extrusion direction refers to the area of ​​a cross section perpendicular to the extrusion direction of the foam board.

[0051] The foam board of the present invention is usually produced by preparing an original board having a size at least one size larger than the desired size, and then cutting the original board to adjust the width, length, and in some cases the thickness.

[0052] However, if the width of the original plate changes significantly during production and becomes narrower than the specified width, it becomes impossible to obtain a foamed board of the specified size, resulting in a poor yield. In addition, in the production of foamed boards, the smaller the apparent density and the larger the cross-sectional area, the more difficult it tends to be to foam. According to the production method of the present invention, since it has excellent production stability, even when a foamed board having a large thickness and a large cross-sectional area is produced, a foamed board with a good appearance can be stably produced. The extruded foamed board, which has a good foaming state and excellent surface smoothness, can be suitably used as a foamed board with a molded skin without cutting the surface in the thickness direction.

[0053] In the case of a foam board used as a heat insulating material, its thickness is preferably 20 mm or more, more preferably 30 mm or more, and even more preferably 50 mm or more, while the upper limit of the thickness is preferably 150 mm, and more preferably 130 mm.

[0054] The width is preferably 800 mm or more, more preferably 900 mm or more, with the upper limit being approximately 1200 mm.

[0055] (Apparent density) The apparent density of the foamed board of the present invention is 20 to 50 kg / m 3and preferably 30 to 40 kg / m 3 When the apparent density is within the above range, the material has sufficient mechanical strength and is lightweight, making it suitable for use as a heat insulating material.

[0056] (Closed bubble rate) The closed cell ratio of the foam board is preferably 85% or more, more preferably 90% or more, and even more preferably 95% or more. If the closed cell ratio is within this range, the foaming agent is likely to remain in the bubbles, and the high heat insulating performance of the foam board can be maintained for a long period of time. In addition, the foam board can have excellent mechanical strength such as compressive strength.

[0057] The closed cell ratio of the extruded foam board in this specification is measured according to procedure C of ASTM-D2856-70 using a Toshiba Beckman Co., Ltd. air comparison type specific gravity meter 930 (a cut sample without a molded skin cut into a size of 25 mm x 25 mm x 20 mm from the extruded foam board is placed in a sample cup and measured. However, if the thickness is too thin to cut a 20 mm cut sample in the thickness direction, for example, two cut samples of a size of 25 mm x 25 mm x 10 mm may be placed in the sample cup at the same time and measured.) using the true volume Vx of the extruded foam board (cut sample) and the closed cell ratio S (%) is calculated using the following formula (1), and the average value of N = 3 is obtained.

[0058] S(%)=(Vx-W / ρ)×100 / (V A -W / ρ) (1) Vx: The true volume (cm) of the cut sample measured by the above method 3 ) (This corresponds to the sum of the volume of the resin that constitutes the cut sample of the extruded foam board and the total volume of the air bubbles in the closed cell portion of the cut sample.) V A : Apparent volume (cm) of the cut sample calculated from the outer dimensions of the cut sample used in the measurement 3 ) W: Total weight of cut sample used for measurement (g) ρ: Density of the resin that composes the extruded foam board (g / cm3 )

[0059] (Bubble structure: average bubble diameter in thickness direction) The average cell diameter in the thickness direction of the foam board is preferably 50 to 200 μm, more preferably 70 to 170 μm, and even more preferably 80 to 150 μm. When the average cell diameter is within the above range, the thermoplastic resin foam board has higher heat insulation properties and superior mechanical strength.

[0060] The method for measuring the average bubble diameter in the thickness direction is as follows: The average bubble diameter in the thickness direction is determined by taking enlarged photographs at three locations, namely, the center and both ends of a cross section perpendicular to the width direction of a foamed board, adjusting the magnification to a range of about 50 to 200 times so that the number of cells in the photograph is about 200 to 500, measuring the maximum diameter of each bubble in the thickness direction on each photograph using image processing software NS2K-pro manufactured by Nano System Co., Ltd., and calculating the arithmetic average of these values.

[0061] (Bubble structure: bubble deformation rate) Further, in the thermoplastic resin foam board, the bubble deformation ratio is preferably 0.7 to 1.5. The bubble deformation ratio is a value calculated by measuring the maximum diameter of each bubble in the width direction of an enlarged photograph of bubbles using image processing software NS2K-pro manufactured by Nano System Co., Ltd., in the same manner as the average bubble diameter in the thickness direction, and dividing the average bubble diameter in the thickness direction by the average bubble diameter in the width direction, and the smaller the bubble deformation ratio is than 1, the flatter the bubbles are, and the larger the bubble deformation ratio is than 1, the longer the bubbles are. When the bubble deformation ratio is within the above range, the thermoplastic resin foam board has excellent mechanical strength and higher thermal insulation. The lower limit of the bubble deformation ratio is more preferably 0.8 from the viewpoint of the compressive strength and dimensional stability of the foam board. Moreover, the upper limit of the bubble deformation ratio is more preferably 1.1, and even more preferably 1.05, from the viewpoint of the effect of improving thermal insulation.

[0062] (Thermal conductivity after 7 days) In the foam board of the present invention, the thermal conductivity 7 days after production is preferably 0.026 W / m·K or less, and more preferably 0.025 W / m·K or less.

[0063] (Thermal conductivity after 100 days) Furthermore, the thermal conductivity 100 days after production is preferably 0.028 W / m·K or less, and more preferably 0.027 W / m·K or less.

[0064] The thermal conductivity can be measured based on the heat flow meter method described in JIS A1412-2:1999 (one test piece, symmetrical configuration, high temperature side 38° C., low temperature side 8° C., average temperature 23° C.). EXAMPLES

[0065] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to these examples in any way.

[0066] In the examples and comparative examples, the following devices and raw materials were used.

[0067] The extrusion device used was a 1st extruder of a high mixing type with an inner diameter of 115 mm and a 2nd extruder with an inner diameter of 180 mm connected in series, a physical foaming agent injection port was provided near the end of the 1st extruder, and a flat die equipped with a resin discharge port (die lip) with a rectangular cross section with a gap of 1 mm and a width of 440 mm was connected to the outlet of the 2nd extruder. In addition, a molding device (guider) consisting of a pair of upper and lower plates made of polytetrafluoroethylene resin, which were horizontally installed at a substantially constant interval, was attached to the resin outlet of the 2nd extruder.

[0068] (1) Base resin (1-1) Polystyrene resin: DIC Corporation polystyrene "HP780AN", melt viscosity (200℃, 100sec -1 )1900 Pa·s (1-2) Polyester resin: spiroglycol modified polyethylene terephthalate "ALTESTER3012" manufactured by Mitsubishi Gas Chemical Co., Ltd., 100% by mass of terephthalic acid, spiroglycol / ethylene glycol = 30% by mass / 70% by mass, melt viscosity (200°C, 100 sec -1 )2000 Pa·s The melt viscosity was measured using a Capillograph 1D (manufactured by Toyo Seiki Seisakusho Co., Ltd.) flow characteristic measuring device at a temperature of 200°C and a shear rate of 100 sec -1 The values ​​were measured under the following conditions.

[0069] (2) Flame retardants (2-1) A flame retardant master batch (GR-134BG manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) containing a mixed flame retardant of 60% by mass of tetrabromobisphenol A bis (2,3-dibromo-2-methylpropyl ether): Daiichi Kogyo Seiyaku's "SR-130" / 40% by mass of tetrabromobisphenol A bis (2,3-dibromopropyl ether): Daiichi Kogyo Seiyaku's "SR-720" was used, and the master batch was added so as to obtain the amount of flame retardant shown in the table. (2-2) Brominated butadiene-styrene copolymer: A flame retardant masterbatch containing Emerald Innovation 3000 (E3000) flame retardant manufactured by LANXESS was used, and the masterbatch was added so as to obtain the amount of flame retardant shown in the table.

[0070] (3) Foam regulator Talc (manufactured by Matsumura Sangyo Co., Ltd., product name "High Filler #12", particle size (d50) 7.5 μm)

[0071] (4) Radiation suppressants (4-1) Graphite (Graphite: manufactured by Resino Color Kogyo Co., Ltd., product name: SBF-T-1683, flake graphite powder, average particle size 17 μm, 40% master batch) (4-2) Titanium oxide (manufactured by Nikko Bix Co., Ltd.)

[0072] (5) Physical foaming agents (A) 1,1,1,4,4,4-Hexafluoro-2-butene (HFO-1336mzz): manufactured by Mitsui Chemours Fluoroproducts (B) Isobutane (C-1) 1,3,3,3-Tetrafluoropropene (HFO-1234ze): manufactured by Honeywell Japan (C-2) Water (C-3) Ethanol: Yamaichi Chemical Industry Co., Ltd.

[0073] Examples 1 to 6, Comparative Examples 1 to 5 The types and amounts of base resin, flame retardant master batch, and cell regulator shown in Table 1 (Examples 1 to 6, Comparative Examples 1 to 5) were fed to a first extruder, heated to 200°C, and kneaded. The types and amounts of physical foaming agents shown in Table 1 were fed from a physical foaming agent injection port provided in the first extruder at the foaming agent injection pressures shown in Table 1, and further kneaded to form a foamable resin melt. Next, the resulting foamable resin melt was transferred to a second extruder to adjust the resin temperature, and then extruded into a guider at a discharge rate of 400 kg / hr. The melt was passed through the guider while foaming to form (shape) a plate-like shape to produce a base plate of a foam plate thickness of 30 mm. Further, the width and length of the base plate were adjusted by cutting, and the molded skins on both sides were evenly cut to produce a rectangular parallelepiped polystyrene resin foam plate (width: 910 mm, length: 1820 mm, thickness: 25 mm, cross-sectional area perpendicular to the extrusion direction: 227.5 cm) without a molded skin. 2 ) was manufactured.

[0074] [Table 1]

[0075] For the foamed boards obtained under the conditions of the Examples and Comparative Examples, the cell structure (average cell diameter in the thickness direction, cell deformation rate), apparent density, closed cell rate, and thermal conductivity (after 7 days and 100 days) were measured by the following methods, and the flammability, appearance (surface smoothness (surface, edge), gas spots, shrinkage), and manufacturing stability were evaluated according to the following criteria. The results are shown in Table 1.

[0076] Bubble structure (average bubble diameter in thickness direction) The average bubble diameter in the thickness direction was determined as follows: Enlarged photographs were taken at a magnification of 100 times at three locations, namely, the center and both ends of the cross section perpendicular to the width direction of the foamed plate, where the foamed plate was divided into two equal parts in the length direction, and the maximum diameter of each bubble in the thickness direction was measured on each photograph using image processing software NS2K-pro manufactured by Nano System Co., Ltd., and the average diameter was calculated by arithmetic mean.

[0077] Bubble structure (bubble deformation rate) The bubble deformation ratio was determined in the same manner as in the method for measuring the thickness direction bubble diameter described above. For an enlarged photograph of the bubbles, the maximum diameter of each bubble in the width direction was measured using image processing software NS2K-pro manufactured by Nano System Co., Ltd., and the average bubble diameter in the width direction was calculated by arithmetically averaging these values, and then the average bubble diameter in the thickness direction was divided by the average bubble diameter in the width direction.

[0078] Specifically, cut samples were cut from the obtained foam board at a position that divided the foam board into two equal parts in the length direction, and at three positions near the center and both ends in the width direction of the foam board, and each cut sample was used as a measurement sample, and the closed cell ratio of each measurement sample was measured to determine the arithmetic average value of the closed cell ratio at the three positions. The cut samples used were cut from the foam board to a size of 25 mm length x 25 mm width x 20 mm thickness.

[0079] S(%)=(Vx-W / ρ)×100 / (Va-W / ρ) (1) In the formula, Vx, Va, W, and ρ are as follows: Vx: The true volume (cm) of the cut sample obtained by measurement using the air comparison type specific gravity meter 3 ) (This corresponds to the sum of the volume of the resin that constitutes the cut sample of the foam board and the total volume of the air bubbles in the closed cell part of the cut sample.) Va: Apparent volume (cm) of the cut sample calculated from the outer dimensions of the cut sample used in the measurement 3 ) W: Total mass of cut samples used for measurement (g) ρ: density of the resin composition constituting the foam board (g / cm3 )

[0080] (Apparent density) The apparent density of the foam board was determined by the following method: A rectangular parallelepiped sample of 50 mm length × 50 mm width × 20 mm thickness was cut from the position where the obtained foam board was divided into two equal parts in the length direction and from the center and both ends in the width direction of the obtained foam board, and the mass was measured and the apparent density of each sample was determined by dividing the mass by the volume, and the arithmetic average of the masses was regarded as the apparent density.

[0081] (Closed bubble rate) The closed cell ratio of the foam board was calculated from the true volume Vx of the foam board measured using an air comparison type specific gravity meter (Toshiba Beckman Co., Ltd., air comparison type specific gravity meter, model: 930) according to procedure C of ASTM-D2856-70, using the following formula (1).

[0082] (Thermal conductivity: 7 days after manufacture) Test pieces measuring 200 mm in length, 200 mm in width, and 20 mm in thickness were cut out from the center of the width of the foamed board immediately after production, and the test pieces were stored in a constant temperature and humidity room at a temperature of 23°C and a relative humidity of 50%. Seven days after production, the thermal conductivity of each test piece was measured based on the flat plate heat flow meter method described in JIS A1412-2 (1999) (two heat flow meter method, high temperature side 38°C, low temperature side 8°C, average temperature 23°C).

[0083] (Thermal conductivity: 100 days after manufacture) The thermal conductivity after 100 days of manufacture is a value obtained by measuring the thermal conductivity of an extruded foam board that has been subjected to test method A of the long-term thermal resistance acceleration test in accordance with JIS A1486:2014. Specifically, a rectangular parallelepiped of 200 mm long x 200 mm wide x 25 mm thick is cut from the center of the width direction of the extruded foam board immediately after manufacture, and then a test piece of 200 mm long x 200 mm wide x 10 mm thick is cut by evenly scraping from both sides, and stored in a constant temperature and humidity room at a temperature of 23 ° C and a relative humidity of 50%, and the thermal conductivity of the test piece after 16 days of manufacture (corresponding to 100 days after the manufacture of a 25 mm thick extruded foam board) was measured based on the flat plate heat flow meter method (two heat flow meter method, high temperature side 38 ° C, low temperature side 8 ° C, average temperature 23 ° C) described in JIS A1412-2 (1999).

[0084] (flammability) Immediately after production, the foam board was stored in a constant temperature and humidity room at a temperature of 23°C and a relative humidity of 50%. Four weeks after production, five test pieces (N=5) were randomly cut out from the foam board. The flammability was measured based on "Test Method A" specified in the flammability test method of JIS A9521:2017, and the flame retardancy of the foam board was evaluated according to the following criteria. Evaluation criteria ◎: Disappeared in less than 2 seconds for all five test pieces ○: Disappeared within 2 to 3 seconds on one or more test pieces, and disappeared within 3 seconds on all five test pieces ×: The average burning time of the five test pieces exceeds 3 seconds (not applicable)

[0085] (Appearance: Surface smoothness (surface, edge)) The surface smoothness of the surface and edges of the original plate and the extruded foam plate were visually evaluated according to the following criteria. ◎: The surfaces and edges of the base plate and extruded foam plate are in excellent condition. ○: The surface or edges of the base plate are rarely rough, but the surface and edges of the extruded foam plate are in excellent condition. △: Roughness rarely occurs on the surface or edges of the extruded foam board. ×: A lot of roughness occurs on the surface or edge of the extruded foam board.

[0086] (Gas Spot) Gas spots (excessively large bubbles observed on the surface and cross section of the foam plate due to separation of the foaming agent generated during extrusion foaming) were evaluated according to the following criteria. ◎: No spot holes were found on the original plate or extruded foam plate. ○: Almost no spot holes were observed in the original plate, and no spot holes were observed in the extruded foam plate. △: Spot holes were observed in some parts of the extruded foam plate. ×: Multiple spot holes were observed in the extruded foam plate, and a good foam plate was not obtained.

[0087] (manufacturing stability) The manufacturing stability was evaluated according to the following criteria. ◎: No variation in width of the original sheet, stable production 〇: The width of the original plate is rarely changed, but this does not affect production. △: Frequent variations in width of the original sheet, and unstable production ×: Difficult to mold the original plate, difficult to manufacture

[0088] From the results of the above measurements and evaluations, Examples 1 to 6, which used 1,1,1,4,4,4-hexafluoro-2-butene (HFO-1336mzz) (foaming agent A) and a saturated hydrocarbon having 3 to 5 carbon atoms (isobutane) (foaming agent B) as the physical foaming agent under the conditions of the present invention, showed good apparent density, cell structure, and thermal conductivity after 7 days and 100 days, and also showed good flammability and appearance.

[0089] In contrast, Comparative Examples 1 to 5, in which a foaming agent was not used under the conditions of the present invention, were inferior in any of smoothness, gas spots, and manufacturing stability, and were inferior in thermal conductivity after 7 days and 100 days compared to Examples 1 to 6.

Claims

1. The method includes a step of extruding a foamable resin composition obtained by kneading a base resin mainly composed of a polystyrene resin, a flame retardant, and a physical foaming agent, and forming the composition into a plate shape using a molding tool. 2 or more, and an apparent density of 20 to 50 kg / m 3 A method for producing an extruded polystyrene foam board, comprising the steps of: The physical blowing agent contains 1,1,1,4,4,4-hexafluoro-2-butene and a saturated hydrocarbon having 3 to 5 carbon atoms, The total amount of the physical foaming agent is 1 to 1.5 mol, the amount of the 1,1,1,4,4,4-hexafluoro-2-butene blended is 0.1 to 0.6 mol per 1 kg of the base resin; the amount of the saturated hydrocarbon having 3 to 5 carbon atoms is 0.2 to 0.7 mol per 1 kg of the base resin, the total amount of the 1,1,1,4,4,4-hexafluoro-2-butene and the saturated hydrocarbon having 3 to 5 carbon atoms is 0.6 to 1.3 mol; A method for producing a polystyrene-based resin extruded foam board, characterized in that the ratio of the amount (mol / kg) of the 1,1,1,4,4,4-hexafluoro-2-butene to the amount (mol / kg) of the saturated hydrocarbon having 3 to 5 carbon atoms (the amount of 1,1,1,4,4,4-hexafluoro-2-butene / the amount of the saturated hydrocarbon having 3 to 5 carbon atoms) is 2 or less.

2. The method for producing a polystyrene-based resin extruded foam plate according to claim 1, characterized in that the ratio of the amount (mol / kg) of the 1,1,1,4,4,4-hexafluoro-2-butene to the amount (mol / kg) of the saturated hydrocarbon having 3 to 5 carbon atoms (the amount of the 1,1,1,4,4,4-hexafluoro-2-butene / the amount of the saturated hydrocarbon having 3 to 5 carbon atoms) is 1.5 or less.

3. The method for producing the polystyrene-based resin extruded foam plate according to claim 1 or 2, characterized in that the physical foaming agent comprises one or more early-dissipation foaming agents selected from the group consisting of water, carbon dioxide, dialkyl ethers with alkyl chains having 1 to 3 carbon atoms, and aliphatic alcohols with 1 to 5 carbon atoms, and the amount of the early-dissipation foaming agent is 0.2 mol or more per kg of base resin.

Citation Information

Patent Citations

  • High-quality polymer foams from fluorinated alkene blowing agents

    JP2010522808A

  • Polystyrene-based resin extrusion foamed board production method and polystyrene-based resin extrusion foamed board

    JP2017125121A

  • Z-HFO-1336mzz blowing agent for foaming thermoplastic polymers, including polystyrene

    JP2019515112A

  • Polystyrene-based resin foamed plate and method for producing the same

    JP2021080424A

  • Hard polyurethane foam

    WO2016136769A1